Pengaruh Pengetahuan Sikap dan Perilaku Masyarakat Dalam Pencegahan Malaria di Desa Mbatakapidu Kabupaten Sumba Timur - Kody, Martha Meti; Abselian, Umbu Putal; Noviana, Ineke (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Malaria is a life-threatening disease caused by a parasite that is transmitted to people through the bite of infected Anopheles mosquitoes and has a clinical picture of fever, anemia, with frequent complaints of lethargy, headache, back pain, chills, bone joint pain, mild fever, stomach ache and others. The high number of malaria cases can threaten the survival of the community, so disease prevention and control efforts are needed to reduce malaria transmission. To prevent the spread of malaria, it is necessary to urge people to clean the environment, close water reservoirs, sleep using mosquito nets, and reduce activities at night. The research method used was pre-experiment with a pre-test and post-test control group design. The sample in the study consisted of 40 people who had suffered, divided into intervention and control groups, with the analysis using non-parametric t-tests. The results of the study showed that there was an influence between community knowledge, attitudes and behavior on malaria prevention in both the intervention group and the control group with a value of p=0.000 (p<0.05). Both groups of respondents experienced an increase in their scores after treatment. In conclusion, there is an influence of community knowledge, attitudes and behavior in preventing malaria.